2016
DOI: 10.1007/s00127-016-1172-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal evolution of the epidemic of charcoal-burning suicide in Japan

Abstract: Our results differ from previous research in other Asian countries (e.g., Taiwan), where the epidemic of charcoal-burning suicide emerged more prominently in urban areas. In Japan, the introduction and diffusion of charcoal burning contributed to a real excess in suicide rates, as well as a widening of the urban/rural disparity in suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…For example, ecological research in Austria showed that suicide rates tended to be significantly higher in rural areas than urban areas among people aged 10-24 and 40-64 years, but no such associations were found for the other age groups [14]. In Japan, previous studies have reported that for men, rural residents had a higher suicide risk compared with urban residents, but not for women [23][24][25]. However, almost all of these studies used mortality data for rather large geographic units (e.g., prefecture), and age-specific analyzes have not been fully explored.…”
Section: Introductionmentioning
confidence: 97%
“…For example, ecological research in Austria showed that suicide rates tended to be significantly higher in rural areas than urban areas among people aged 10-24 and 40-64 years, but no such associations were found for the other age groups [14]. In Japan, previous studies have reported that for men, rural residents had a higher suicide risk compared with urban residents, but not for women [23][24][25]. However, almost all of these studies used mortality data for rather large geographic units (e.g., prefecture), and age-specific analyzes have not been fully explored.…”
Section: Introductionmentioning
confidence: 97%
“…In South Korea, the number of suicide deaths by charcoal burning rose from 34 in 2006 to 1,125 in 2012 (Choi et al, 2014). In many cases, the rise in suicide by charcoal burning was associated with an increased overall rate of suicide (Chang et al, , 2010Thomas et al, 2011;Yip et al, 2010;Yoshioka et al, 2016Yoshioka et al, , 2014. People living in urban areas were found to be at higher risk likely because of greater access to both the charcoal itself and media exposures (Chang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“… 13 16 17 Initially, in also Japan, internet involvement was noted, as young Japanese charcoal-burning suicides were involved in several suicide agreements on charcoal-burning suicides. 13 34 35 In 2005, a voluntary guideline was regulated by associations managing internet provider service in Japan to suppress suicidal attempts via internet 35 without implementation of direct means restrictions against charcoal burning 17 ; however, charcoal-burning suicide continued to increase until 2009. In the present study, municipal DLL and ELM decreased male and female suicide mortalities, respectively.…”
Section: Discussionmentioning
confidence: 99%